Comparative assessment of venous congestion severity and hospitalization outcomes in patients with acute decompensated heart failure with preserved ejection fraction - E. A. Rogozhkina; T. Yu. Vedenikin; Yu. S. Timofeev; A. A. Ivanova; A. R. Afaunova; O. N. Dzhioeva; O. M. Drapkina (Российский кардиологический журнал, 2024)
Aim. To characterize the potental of additional paraclinical research methods (ultrasound, determination of body composition) for assessing the congestion severity in patients with acute decompensated heart failure with preserved ejection fraction (ADHFpEF) in the intensive care unit.Material and methods. We examined 82 patients with ADHFpEF aged from 50 to 85 years, who were hospitalized in the intensive care unit of the Veresaev City Clinical Hospital (Moscow). All patients underwent a standard clinical and laboratory examination, including determination of NT-proBNP, as well as echocardiography, chest radiography, bioimpedance analysis, Venous Excess Ultrasound (VExUS), lung ultrasound. Depending on the congestion degree visualized by VExUS, patients were divided into three groups.Results. The median levels of NT-proBNP, E/A and E/e', number of B-lines in one lung segment, ECW and TBW, and the diuretics' dose used in the hospital in pa tients with ADHFpEF and severe congestion were significantly higher. Signs of congestion obtained as a result of X-ray examination did not differ significantly between groups. In-hospital death was associated with higher values of NT-proBNP, E/A ratio, IVC diameter, number of B-lines in one lung segment, ECW and TBW. The odds of death in patients with VExUS Grade 3 increased 20,9 times compared to Grade 1 (95% CI: 1,125-387,688).Conclusion. Higher levels of NT-proBNP, the dose of diuretics used in the hospital, and ECW and TBW were associated with congestion severity. The severity of congestion assessed by VExUS and ECW/TBW are positively associated with inhospital mortality